Not Dead Enough - Neiheiser, Tyffany D (New York : Viking, 2024)
"Charlotte survived the car crash that killed her boyfriend Jerry, but that night, everything changed. Charlotte wants desperately to get back to "normal," --whatever that means now-- and start reconnecting with friends she hasn't spoken to in months. And she's trying to work through her PTSD with the help of her therapist, only she can't tell the truth about Jerry or what really happened the night he died. Just when Charlotte thinks she might be moving on, someone starts sending her threatening messages claiming to be Jerry, saying things only he would know. But it can't really be Jerry because there's no such thing as ghosts. The cold spots in her room must be a draft and the noises she hears must be the house creaking. There has to be a logical explanation for all of it. Because if ghosts are real, then Jerry came back for her-just like he always said he would"--.
new ya book winter 2024.
Keywords: Traffic accidents -- Juvenile fiction; Secrecy -- Juvenile fiction; Post-traumatic stress disorder -- Juvenile fiction; Dating violence -- Juvenile fiction; Secrets -- Fiction; Dating violence -- Fiction; Traffic accidents -- Fiction; Post-traumatic stress disorder -- Fiction; Novels; Romans; Thriller fiction; Horror fiction